2022
DOI: 10.32920/ryerson.14646477.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Service needs and gaps for international students transitioning to permanent residency in a "two-step" immigration process : a Toronto-based study

Abstract: Despite the increase in efforts to attract and retain international students in Canada, including the introduction of the Canadian Experience Class in 2008, there has been little investigation into what supports will assist international students as they transition from students to workers to migrants. This research paper is a Toronto-based investigation of the service needs and gaps that exist for international students aiming to transition to permanent residency in Canada. Data gathered from interviews with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…These barriers stem from employers' preference for Canadian work experience; the challenge of language and cultural adaptability to Canadian workplaces; and students' perceived barriers. Roach (2011) conducted interviews at international student offices in four Toronto post-secondary institutions. She found that Canadian employers "discriminate against international students' lack of Canadian work experience" (2011, p.39).…”
Section: Lack Of Employment Preparation and Obstacles To Labour Marke...mentioning
confidence: 99%
See 2 more Smart Citations
“…These barriers stem from employers' preference for Canadian work experience; the challenge of language and cultural adaptability to Canadian workplaces; and students' perceived barriers. Roach (2011) conducted interviews at international student offices in four Toronto post-secondary institutions. She found that Canadian employers "discriminate against international students' lack of Canadian work experience" (2011, p.39).…”
Section: Lack Of Employment Preparation and Obstacles To Labour Marke...mentioning
confidence: 99%
“…There are inconsistency and lack of qualification and resources in service delivery by international student offices across institutions in Canada. Roach (2011) who studied service needs and gaps related to international students' services found "differential service provisions" exist across institutions (p. 29). For instance, the study revealed that only one international student office among the four that participated in this study could refer international students to "service providers in the community for extended support or settlement services" (Roach, 2011, p. 29).…”
Section: Limitations Of Services Offered By Offices Serving Internati...mentioning
confidence: 99%
See 1 more Smart Citation